2006
DOI: 10.1074/jbc.m605525200
|View full text |Cite
|
Sign up to set email alerts
|

Loss of N-Linked Glycosylation Reduces Urea Transporter UT-A1 Response to Vasopressin

Abstract: The vasopressin-regulated urea transporter (UT)-A1 is a transmembrane protein with two glycosylated forms of 97 and 117 kDa; both are derived from a single 88-kDa core protein.However, the precise molecular sites and the function for UT-A1 N-glycosylation are not known. In this study, we com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 31 publications
2
55
0
Order By: Relevance
“…Cells were grown on Transwell filters to confluence. Before immunostaining, cells were rinsed twice with PBS, fixed with 4% formalin in PBS for 10 -15 min at 4°C, washed with PBS three times, permeabilized in PBS containing 0.1% Triton X-100 for 10 min, and blocked with 1% bovine serum albumin in PBS (blocking buffer) for 30 min at 25°C (27). Cells were then incubated with primary antibody, anti-UT-A1 (C-terminal), diluted 1:4000 in blocking buffer for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were grown on Transwell filters to confluence. Before immunostaining, cells were rinsed twice with PBS, fixed with 4% formalin in PBS for 10 -15 min at 4°C, washed with PBS three times, permeabilized in PBS containing 0.1% Triton X-100 for 10 min, and blocked with 1% bovine serum albumin in PBS (blocking buffer) for 30 min at 25°C (27). Cells were then incubated with primary antibody, anti-UT-A1 (C-terminal), diluted 1:4000 in blocking buffer for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma Membrane Isolation-Plasma membrane isolation of UT-A1-MDCK cells was performed as described previously (27) with some modification. Ad-snapin-infected UT-A1-MDCK confluent cells (in 6-well plates) were treated with 10 M forskolin (FSK, Sigma) for 20 min and then frozen at Ϫ80°C for 1 h. The cell pellets were collected and resuspended in icecold homogenization buffer (250 mM sucrose, 2 mM EDTA, 10 mM Tris, pH 7.4) containing protease inhibitor mixture (Sigma) at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Reminiscent of its effect on several other membrane transport proteins, such as AQP2, 23 NKCC2, 24 and ENaC, 25 N-linked glycosylation is critical for UT-A1 membrane trafficking, stability, and activity. 8,10 Animal studies revealed a functional link between UT-A1 activity and its glycosylation state. In particular, the highly glycosylated 117-kD form of UT-A1 is increased in several conditions associated with decreased urine concentration, such as STZ-induced diabetes mellitus, 19 a low-protein diet, 26 hypercalcemia, 27 water diuresis, 26 and furosemide administration.…”
Section: Discussionmentioning
confidence: 99%
“…Only Asn279 and Asn742 in the two large extracellular loops are proven to be sites for N-linked glycosylation. 10 Importantly, loss of glycosylation by mutating the two glycosylation sites significantly impairs the response of UT-A1 to vasopressin. 10 Vasopressin is the primary hormone regulating UT-A1 transport activity in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation